Optimizing the Functions of the Great Mosque of Pinrang in the Development of Islamic Da'wah - Muh. Ilham H; M. Nasri H; Nurhikmah Nurhikmah (Institut Agama Islam Negeri Parepare, 2022)
This research method uses a qualitative descriptive approach. This qualitative approach intends to produce descriptive data in the form of speech or action from the observed subject, both written and unwritten. The data collection techniques used are field research such as interviews, observations, and documentation. The results of this study indicate that the optimization carried out at the Pinrang Grand Mosque in developing Islamic Da'wah has been running in an orderly and directed manner, this is supported by the system. in the Pinrang Grand Mosque has been running well in accordance with management functions such as, planning (takhtith), organizing (al-thanzim), implementation (tawjih), and supervision (riqobah), then the next supporting factor is the mosque management system such as Idara, Imarah, and Riayah, where these three systems work together with Management functions in maximizing the work program activities at the Pinrang Grand Mosque, especially in the work program for the development of Islamic Da'wah.